OPTIMAL PHARMACOTHERAPY STRATEGIES IN HYPERTENSION MANAGEMENT: COST ANALYSIS AND DRUG CLASS STRUCTURE (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the characteristics of antihypertensive drug utilization at a specialized hospital in Thu Duc city, Ho Chi Minh city.Subjects and methods: A cross-sectional descriptive study was conducted using retrospective data from 102,948 treatment visits of hypertensive patients (I10 according to ICD-10) covered by health insurance at Thu Duc General Hospital from January to September 2024. Data extracted from electronic medical records included patient characteristics (presence and types of comorbidities), prescribed medications belonging to five guideline-recommended drug classes (angiotensin-converting enzyme inhibitors, angiotensin II receptor blocker, calcium channel blockers, diuretics, and beta blockers), and medication costs. Data analysis was performed using Microsoft Excel software.Results: Of the 102,948 treatment visits, 99.6% were outpatient encounters, and 93.5% involved patients with comorbidities, predominantly dyslipidemia and cardiovascular diseases. Dyslipidemia was present in 68.8% of inpatient cases and 81.7% of outpatient cases, while chronic kidney disease accounted for 18.4% of inpatient and 3.8% of outpatient cases. Angiotensin II receptor blocker (62.1%), beta blockers (55.9%), and calcium channel blockers (52.9%) were the most frequently utilized drug classes, with angiotensin II receptor blocker contributing to 50% of total medication expenditures. The three most prescribed active ingredients were Bisoprolol, Amlodipine, and Hydrochlorothiazide, each appearing in more than 10% of treatment visits.Conclusion: The findings reflect current hypertension management practices in Vietnam, highlighting strengths in drug selection and individualized therapy. Nonetheless, further optimization is needed to enhance treatment effectiveness and reduce medication costs.
Keywords: Drug utilization, hypertension, comorbidity, medication management, clinical guidelines.